2013
DOI: 10.3892/or.2013.2534
|View full text |Cite
|
Sign up to set email alerts
|

Role of GLI-1 in epidermal growth factor-induced invasiveness of ARCaPE prostate cancer cells

Abstract: Abstract. Epidermal growth factor (EGF) signaling and Hedgehog (HH) signaling are both involved in prostate cancer (PCa) progression, yet the mechanisms through which these two pathways are synergistically linked require elucidation. In the present study, we aimed to ascertain how EGF and the HH signaling transcription factor GLI-1 are linked in prostate cancer invasiveness. ARCaP human prostate cancer cells, which included ARCaP E and ARCaP M cells, were used as a model in the present study. The expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Eotaxin-1 induces the activation of ERK1/2 in prostate cancer cells. The ERK pathway is essential to the invasion and metastasis of prostate cancer (14). Here, we detected the phosphorylation of ERK1/2 following eotaxin-1 treatment by western blotting.…”
Section: Eotaxin-1 Increases the Expression Of Mmp-3 In Du-145 Cellsmentioning
confidence: 96%
“…Eotaxin-1 induces the activation of ERK1/2 in prostate cancer cells. The ERK pathway is essential to the invasion and metastasis of prostate cancer (14). Here, we detected the phosphorylation of ERK1/2 following eotaxin-1 treatment by western blotting.…”
Section: Eotaxin-1 Increases the Expression Of Mmp-3 In Du-145 Cellsmentioning
confidence: 96%
“…Authors hypothesized that the mediator of EGF and HH pathway crosstalk is ERK1/2 through an unknown mechanism [125].…”
Section: Prostate Cancermentioning
confidence: 99%
“…Therefore, agents that target Smoothened (Smo) or upstream targets of the Hh pathway remain largely ineffective in these cancers (15,16), suggesting the importance of the development of small molecule inhibitors that may target Glis, particularly Gli1. Although Gli1 is often an up-regulated Hh component in many tumors, identification of the signaling mechanisms it regulates in tumor cells is critical in developing effective therapeutic modalities (17)(18)(19)(20). Recently, several studies indicated the influence of Hh/Gli1 signaling on DNA damage response (DDR) 3 and repair pathways to promote more aggressive disease and tumor resistance to therapeutics (21)(22)(23)(24).…”
Section: Aberrant Expression Of Hedgehog Molecules Particularlymentioning
confidence: 99%